GAMBARAN LOYALITAS MEREK PADA KONSUMEN STARBUCKS COFFEE - Clara Moningka; Fransiska Fransiska (Universitas Bunda Mulia, 2011)
Today’s globalization has tightened the competition between global and local brand. Within the competition between local and global brand that particularly has been increasingly developed in Indonesia lately, what a company need is a brand loyalty. Brand loyalty is a regular buying of a particular brand that is consistent over a long period of time because of one’s emotional attachment toward this particular brand. One famous global brand that has been turned iconic from it’s main product is Starbucks Coffee. Started in 1971, today Starbucks has become a global brand that continuously expands their business including to Indonesia. This research investigates the brand loyalty in Starbucks consumers. Additional measurement is Consumer Ethnocentrism Scale (CETSCALE). Data were collected from 200 Starbucks consumer in Jakarta’s area. Statistical method used is Pearson Product Moment Coeficient of Correlation. The result shows r = 0.682, p=.001 < .05. Data tested concluded that there is a significant relationship between brand perception and brand loyalty. Keywords: Global brand, consumer perception, Starbucks, brand loyalty